Development of Kahoot-Based Learning Evaluation Instruments on Plant Parts Material - Nur'Aini Kamilah (Indonesian Journal of Education and Social Studies, 2026)
This study aimed to develop and examine the feasibility and effectiveness of a Kahoot-based learning evaluation instrument on the topic of plant body parts for fourth-grade elementary students. The study was motivated by the continued reliance on conventional paper-based evaluation tools, which tend to limit student engagement, motivation, and conceptual understanding. A Research and Development (R&D) approach was employed using the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations, interviews, expert validation sheets, student response questionnaires, and pre-test and post-test instruments. Product validation involved media experts, language experts, and subject matter experts to ensure the quality of the evaluation instrument in terms of content accuracy, language clarity, and media design. The validation results indicated that the developed instrument achieved a very high level of feasibility. Student responses also demonstrated strong acceptance and positive engagement with the Kahoot-based evaluation. In terms of effectiveness, the results showed a substantial improvement in students’ learning outcomes, as reflected by a notable increase in post-test scores compared to pre-test scores and a high N-gain category. These findings suggest that the Kahoot-based evaluation instrument is not only pedagogically appropriate but also effective in enhancing student motivation and learning achievement. Therefore, the integration of game-based digital evaluation tools such as Kahoot can serve as a viable alternative to traditional assessment methods and contribute to more interactive and meaningful learning evaluation practices in elementary education.